An experimental study on friction stir processing of aluminium alloy (AA-2024) and boron nitride (BNp) surface composite. (2022) - Boopathi, Sampath; Jeyakumar, M.; Singh, G. Robert; King, Francis Luther; Pandian, M.; Subbiah, Ram; Haribalaji, V.
Abstract: In this research, the influences of percentages of boron nitride powder (BNp ) on the characteristics of friction stir Aluminium alloy (AA-2024) surface composite has been studied. Taguchi method has been used to design and investigate the effect of volume percentage of BNp, welding speed, and tool rotational speed on tensile strength and wear rate of surface composite. AA-2024 alloy has been used in aerospace and automotive industries due to its low weight-high strength. The optimum tensile strength and wear rate have been estimated and validated by confirmation experiments. The specimen made for confirmation experiments have been used to examine the fractures microstructure. The maximum tensile strength and minimum wear rate of the optimum specimen are 594 MPa and 1.37 mm 3 /Nm respectively. The optimum process parameters settings: 15% of BNp, 1200 rpm of tool rotation speed, and 50 mm/min welding speed. It was also observed that the volume percentage of BNp and tool rotational speed are significant FSP parameters on tensile strength and wear rate.